Rastreamento da máxima potência em conexão série de sistemas fotovoltaicos utilizando o controle granular - Garcia, Rodolpho Cordeiro (2017)
Considering the use of energy from photovoltaic (PV) systems, this work presents a comparative study of the traditional PV system with the multi-string PV system. The traditional system consists of three PV panels associated in series and connected to the Boost DC-DC converter. The Perturb & Observe (P&O) algorithm is used to perform the maximum power point search (MPP). On the other hand, traditional systems can be influenced by partial shading when a nonuniform solar irradiation occurs on the PV array, so it is compared to a multi-string system, which consists of three DC-DC Boost converters, Where each inverter has a single PV panel connected to its input, and the output of the inverters are connected in series and connected to a DC bus. In the multi-string system two different MPP (MPPT) traces were used, the first one is called a simple variable distributed (SV-P&O), which uses the P&O algorithm for each upconverter, which operates verifying the variation Of power of each PV panel, necessitating the reading of the voltage and output current of each panel, that is, a total of six sensors are required. On the other hand, the second methodology called multivariate granular control (MV-P&O), operates by verifying the power variation in the output on the DC bus, that is, requires only two sensors. By means of results obtained by computational simulations, the systems are evaluated and compared, considering the operation of the system without shading and partial shading.